Genetic variability detection in Brahman cattle in Brazil trough pedigree analysis - de Faria, Lydio Cosac; de Queiroz, Sandra Aidar; Vozzi, Pedro Alejandro; Lôbo, Raysildo Barbosa; Magnabosco, Cláudio de Ulhôa; de Oliveira, João Ademir (Pesquisa Agropecuaria Brasileira, 2011)
This work aimed to analyse the genetic variability of Brahman breed in Brazil, through the analysis of 15,851 pedigrees. The data file was divided into two periods: 1998–2001 and 2002–2005. The genetic variability was evaluated by the following parameters, based on the probability of gene origin: number of ancestors, effective number of founders, effective number of remaining genomes, and the relationship and inbreeding coefficients. The values for the number of founders showed that the population is expanding, although the effective number of founders has been reduced from one period to the other. The results were different for the number of ancestors and the remaining genomes, which grew by 23% in the studied periods. The inbreeding coefficient decreased in the studied periods, but the "inter se" relationship coefficient increased. Few ancestors showed great genetic contribution to the population, which indicates the use of small number of individuals in the reproduction. Brahman breed population in Brazil is expanding, characterized by the decreasing of the inbreeding coefficients and the increasing of the effective number of ancestors and remaining genotypes. Nevertheless, the breed genetic variability shows increasing "inter se" relationships and a great concentration of gene heritage of few individuals in the population.